2010
DOI: 10.1001/archophthalmol.2010.361
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Residual or Recurrent Esotropia Following Maximal Bilateral Medial Rectus Recession

Abstract: To describe the effect of graded unilateral vs bilateral lateral rectus resection in the treatment of residual or recurrent esotropia after maximal medial rectus muscle recession. Methods: Retrospective case series of children with residual or recurrent esotropia. All children underwent initial eye muscle surgery for angles of 40 to 60 prism diopters (medial rectus recession of 5.5-6.5 mm; 11.0-11.5 mm from surgical limbus). If significant esotropia persisted or recurred, surgical results from graded lateral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Our results are in agreement with Morrison et. al [11] who reported of no significant difference in surgical response per millimeter between first and second surgery. Therefore, they recommended that residual deviations larger than 15 PD need to be addressed with bilateral surgery [11].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our results are in agreement with Morrison et. al [11] who reported of no significant difference in surgical response per millimeter between first and second surgery. Therefore, they recommended that residual deviations larger than 15 PD need to be addressed with bilateral surgery [11].…”
Section: Discussionmentioning
confidence: 96%
“…al [11] who reported of no significant difference in surgical response per millimeter between first and second surgery. Therefore, they recommended that residual deviations larger than 15 PD need to be addressed with bilateral surgery [11]. Looking at our data from the first surgery, the amount of maximal medial rectus recession was 6.5-7.0 mm for each muscle, even when esotropia measured to be more than 50 PD.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Limited data are available on the amount of correction gained with each millimeter of BLR resection. One reason for the wide range of reported successful outcomes for BLR resection, ranging from 52% to 87%, 5 6 7 8 is related to the diverse surgical dosage used during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…5 6 There is a limited amount of data on the extent of correction gained with each millimeter of BLR resection. 7 8 Our experience has shown that resection based on surgical tables for unoperated muscles can cause overcorrection. Thus, we chose numbers that were 0.5 mm less than the proposed numbers in the standard table for primary BLR resection without a history of BMR recession given that the antagonist's muscles are weak here.…”
Section: Introductionmentioning
confidence: 99%